Circulating tumour cells and circulating nucleic acids as a measure of tumour dissemination in non-metastatic colorectal cancer surgery. Issue 3 (March 2015) - Lim, S.H.; Spring, K.J.; de Souza, P.; MacKenzie, S.; Bokey, L.
Abstract There is accumulating evidence for circulating tumour cells (CTCs) and circulating tumour nucleic acids (ctNAs) as prognostic and predictive biomarkers in colorectal cancer. Their role in the perioperative setting is evolving. These blood-borne biomarkers can potentially demonstrate tumour dissemination at time of colorectal cancer surgery and estimate the completeness of a surgical resection. CTCs and circulating ctNA levels at time of surgery, and persistent levels post-surgery, may correlate with poorer patient outcomes. These biomarkers can be utilised to refine surgical techniques to minimise tumour dissemination and determine the need for adjuvant therapy.